(3u-7)(2-u)=0

Simple and best practice solution for (3u-7)(2-u)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3u-7)(2-u)=0 equation:


Simplifying
(3u + -7)(2 + -1u) = 0

Reorder the terms:
(-7 + 3u)(2 + -1u) = 0

Multiply (-7 + 3u) * (2 + -1u)
(-7(2 + -1u) + 3u * (2 + -1u)) = 0
((2 * -7 + -1u * -7) + 3u * (2 + -1u)) = 0
((-14 + 7u) + 3u * (2 + -1u)) = 0
(-14 + 7u + (2 * 3u + -1u * 3u)) = 0
(-14 + 7u + (6u + -3u2)) = 0

Combine like terms: 7u + 6u = 13u
(-14 + 13u + -3u2) = 0

Solving
-14 + 13u + -3u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(-7 + 3u)(2 + -1u) = 0

Subproblem 1

Set the factor '(-7 + 3u)' equal to zero and attempt to solve: Simplifying -7 + 3u = 0 Solving -7 + 3u = 0 Move all terms containing u to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3u = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 3u = 0 + 7 3u = 0 + 7 Combine like terms: 0 + 7 = 7 3u = 7 Divide each side by '3'. u = 2.333333333 Simplifying u = 2.333333333

Subproblem 2

Set the factor '(2 + -1u)' equal to zero and attempt to solve: Simplifying 2 + -1u = 0 Solving 2 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1u = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1u = 0 + -2 -1u = 0 + -2 Combine like terms: 0 + -2 = -2 -1u = -2 Divide each side by '-1'. u = 2 Simplifying u = 2

Solution

u = {2.333333333, 2}

See similar equations:

| 12y=-48 | | 3x^2+45x-168= | | Q+14=8(1q+7) | | 4(y+9)(-y-1)=0 | | 1/2x=34+4x | | -40=8w | | 30=-5s | | 8x-28=-6(7-x) | | 3y-36=2y | | -28=7n | | 3/16.8 | | 2m=6m-20 | | -61=-48+c | | -.25x+3.5=-.625 | | -2(5+2r)=-6-5r | | 1/3x-3=-2 | | (3-z)(3z+4)=0 | | 81x^2-27x-18=0 | | 94=t+6 | | T^3-12t^2+45t+2=0 | | 6y+7/5 | | 4x+6y=-30 | | 5(b+1)=2(b-5) | | 5u(u-8)(u-6)=0 | | 5a-8whena=9 | | 5b+5=2b-10 | | 3x+15=57 | | y-79=-61 | | -(1+5n)=-4n | | 2x+4y=122 | | 73-6x=3x+23 | | 2x+19=-79-9x |

Equations solver categories